Synthesis of novel amine modified hollow mesoporous silica@Mg-Al layered double hydroxide composite and its application in CO2 adsorption - Yilmaz, Muge Sari (ELSEVIER SCIENCE BV, 2017)
In this study, novel amine modified hollow mesoporous silica (HMS)@Mg-Al layered double hydroxide (LDH) composite was successfully prepared in order to evaluate its CO2 adsorption capacity. Pure and amine modified HMS composite, and HMS@Mg-Al LDH adsorbents were also prepared for the cornparison of their CO2 adsorption capacities. The prepared adsorbents were characterized using X-ray diffraction (XRD), elemental analysis (EA), thermogravimetric analysis (TGA), N-2 adsorption/desorption, Fourier transform infrared (FTIR) and transmission electron microscopy (TEM) techniques. CO2 adsorption performances of the adsorbents at different temperatures were determined using a TGA system. The amine modified HMS@Mg-Al LDH and the amine modified HMS showed maximum CO2 adsorption capacities of 1.28 and 1.57 mmol g(-1), respectively, at 75 degrees C. Furthermore, compared to other adsorbents, the amine modified HMS@Mg-Al LDH composite had the highest adsorption capacity at 25 degrees C. The CO2 adsorption isotherms on all the adsorbents were measured using a volumetric method, and the CO2 isotherms were evaluated by applying the Langmuir and Freundlich models. The Langmuir model fit well with the amine modified samples, while the Freundlich model fit well with pure samples. The amine modified adsorbents exhibited stable adsorption performance throughout four consecutive adsorption/desorption cycles. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Novel composite; Hollow mesoporous silica; Layered double hydroxide; Amine modification; CO2 adsorption; CARBON-DIOXIDE ADSORPTION; ZEOLITE; CAPTURE; Chemistry; Science & Technology - Other Topics; Materials Science